2011
DOI: 10.1093/neuonc/nor188
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion tensor magnetic resonance tractography in predicting the extent of resection in glioma surgery

Abstract: Diffusion tensor imaging (DTI) tractography enables the in vivo visualization of the course of white matter tracts inside or around a tumor, and it provides the surgeon with important information in resection planning. This study is aimed at assessing the ability of preoperative DTI tractography in predicting the extent of the resection achievable in surgical removal of gliomas. Patients with low-grade gliomas (LGGs; 46) and high-grade gliomas (HGGs; 27) were studied using a 3T scanner according to a protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 42 publications
7
91
0
5
Order By: Relevance
“…To date, this has been reported mostly in supratentorial tumor surgery (18,36). Previous studies have reported that for supratentorial lesions, preoperative CST involvement may be a predictor of motor deficit and that postoperative improvement, or normalization, of the CST was a predictor of clinical improvement (3,4,9).…”
Section: Discussionmentioning
confidence: 99%
“…To date, this has been reported mostly in supratentorial tumor surgery (18,36). Previous studies have reported that for supratentorial lesions, preoperative CST involvement may be a predictor of motor deficit and that postoperative improvement, or normalization, of the CST was a predictor of clinical improvement (3,4,9).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative brain mapping studies have recently demonstrated that DTI tractography data are accurate to describe the trajectory of tracts when infiltrated by tumor, as tracking results correlated with those obtained by direct electrical stimulation. 2,4 Consequently, the complete disruption of the tract may predict the absence of eloquent subcortical areas, increasing the likelihood of a greater resection. In the case presented in Fig.…”
Section: Tract Identification and Extent Of Insular Glioma Resectionmentioning
confidence: 99%
“…In this study, it was found that patients with intact white matter fiber tracts or fascicles on DTI had a higher likelihood of complete resection compared with patients with infiltrated or displaced fascicles. [51] Functional mapping for patients with low-grade gliomas in suspected eloquent regions of the brain has also been suggested as a tool to improve delineation of true functional and non-functional areas to maximize tumor resection while maintaining function. [52] In addition to multiparametric MRI, several groups have demonstrated the utility of MET PET in guiding surgery and radiation treatment planning of brain tumors.…”
Section: Use Of Advanced Imaging To Guide Surgery and Radiotherapymentioning
confidence: 99%